Retrofit of water network with optimization of existing regeneration units - Tan, Yin Ling; Manan, Zainuddin Abdul (American Chemical Society, 2006)
Grassroots synthesis of a maximum water recovery network based on pinch analysis has been rather well-established. In contrast, less work has been done on water network retrofit, particularly those involving the optimization of regeneration units. Optimization of the regeneration units provides room for further utility savings and avoids the installation of new regeneration units. This paper presents a new systematic methodology for water network retrofit involving the optimization of existing regeneration units. The procedure begins with setting the minimum utility targets for a water network, and application of some process changes heuristics to choose the best optimization scheme for existing regeneration units. Next, utility savings and capital investment targets were established for the chosen optimization scheme. The existing water network was finally retrofitted to realize the economic targets.